Supply Curves and Maximum Satisfaction - Meriam, R. S. (Quarterly Journal of Economics, 1928)
I. The decreasing cost schedule as a schedule of uniform or average cost, 170. — Incompatible with rent, 170. — Marshall's particular expenses curve and its uses, 171. — II. Professor Knight's prediction that an increased demand increases normal price, 175. — It ignores possible economies, 177. — It overlooks reduced demand elsewhere, 178. — III. The possibility of increasing cost, 180. — Professor Sraffa's view, 181. — Professor Pigou's view, 183. — Professor H. E. Miller on consumers' surplus, 185. — IV. The maximum satisfaction doctrine, 189. — Professor Pigou's statement, 189. — Marshall's treatment, 190. — Method and assumptions in dealing with the tax and the bounty as one problem, 191. — Four cases, 193. — The general conclusion, 196.